The Hoard of Roman Republican Weapons from Grad near Šmihel - Horvat, Jana (Arheološki vestnik, 2002)
A hoard of Roman weapons was discovered around 1890 at the prehistoric settlement of Grad near Šmihel under Nanos Mt. The circumstances of the find, all of the material, and the typology of the weapons are presented in the article. Weapons for fighting at a distance predominated: heavy and light pila, incendiary pila, javelins, catapult bolts, and arrowheads. Many of them were deformed – evidently previously used in battle. Considering the pila with flat hafts, the hoard could be dated to the end of the 3rd and the first half of the 2nd cent. BC, while the historical circumstances would indicate a burial in the first half of the 2nd cent. BC. The late La Tène and Roman chance finds from Grad are analyzed at the end, as is the question of the settlement in the La Tène and Roman periods.